Dehydrocostus lactone suppresses gastric cancer progression by targeting ACLY to inhibit fatty acid synthesis and autophagic flux - Yuxuan Chen; Junyu Shen; Mengyun Yuan; Huaizhi Li; Yaqi Li; Shanshan Zheng; Bo Han; Cancan Zhang; Shenlin Liu; Qingmin Sun; Jian Wu (Journal of Advanced Research)
Introduction: Dehydrocostus lactone (Dehy), a natural sesquiterpene lactone from Saussurea lappa Clarke, displays remarkable efficacy in treating cancer and gastrointestinal disorders. However, its anti-gastric cancer (GC) effect remains poorly understood. Objectives: Our study aimed to elucidate the anti-GC effect of Dehy and its putative mechanism. Methods: The anti-GC effect was assessed with MTT, colony formation, wound healing and transwell invasion assays. Cell apoptosis rate was detected by Annexin V-FITC/PI binding assay. Network pharmacology analysis and XF substrate oxidation stress test explored the underlying mechanism and altered metabolic phenotype. Lipogenic enzyme expressions and neutral lipid pool were measured to evaluate cellular lipid synthesis and storage. Biolayer interferometry and molecular docking investigated the direct target of Dehy. Autophagosomes were observed by transmission electron microscopy and MDC staining, while the autophagic flux was detected by mRFP-GFP-LC3 transfection. The clinical significance of ACLY was confirmed by tissue microarrays. Patient-derived xenograft (PDX) models were adopted to detect the clinical therapeutic potential of Dehy. Results: Dehy prominently suppressed GC progression both in vitro and in vivo. Mechanistically, Dehy down-regulated the lipogenic enzyme ACLY, thereby reducing fatty acid synthesis and lipid reservation. Moreover, IKKβ was identified as the direct target of Dehy. Dehy inhibited the phosphorylation of IKKβ, promoting the ubiquitination and degradation of ACLY, thereby resulting in lipid depletion. Subsequently, GC cells initiated autophagy to replenish the missing lipids, whereas Dehy impeded this cytoprotective mechanism by down-regulating LAMP1 and LAMP2 expressions, which disrupted lysosomal membrane functions, ultimately leading to apoptosis. Additionally, Dehy exhibited potential in GC clinical therapy as it enhanced the efficacy of 5-Fluorouracil in PDX models. Conclusions: Our work identified Dehy as a desirable agent for blunting abnormal lipid metabolism and highlighted its inhibitory effect on protective autophagy, suggesting the future development of Dehy as a novel therapeutic drug for GC.